Biological and enzymatic treatment of bisphenol A and other endocrine disrupting compounds: a review. (September 2013) - Husain, Qayyum; Qayyum, Shariq
Abstract : Bisphenol A is predominantly used as an intermediate in the production of polycarbonate plastics and epoxy resins. Traces of bisphenol A released into the environment can reach into the wastewater and soil via application of sewage sludge from wastewater treatment systems that receive water containing bisphenol A, or from leachate from uncontrolled landfills. In this study we have made an effort to review the work on the presence of bisphenol A and other related endocrine disrupting compounds in the environment and their impact on the life of living organisms including human beings. Bisphenol A has several implications on the health of human beings as well it can also affect the growth of plants and animals. Number of physicochemical methods such as adsorption, membrane based filtration, ozonation, fenton, electrochemical and photochemical degradation has been used for the removal of bisphenol A. However, these methods have some inherent limitations and therefore cannot be used for large scale treatment of such pollutants. The alternative procedures have attracted the attention of environmental scientists. Biological methods are looking quite promising and these procedures are helpful in the complete degradation of bisphenol A and related compounds. Several bacterial, fungal, and algal strains and mixed cultures have successfully been employed for the degradation of bisphenol A. Recently, enzymatic methods have attracted the attention of the environmentalists for the treatment of bisphenol A and other endocrine disrupting compounds. Numerous types of oxidoreductases; laccases, tyrosinases, manganese peroxidase, lignin peroxidase, polyphenol oxidases, horseradish peroxidase and bitter gourd peroxidase have exhibited their potential for the remediation of such types of compounds. The cytochrome P 450 monooxygenases and hemoglobin have also participated in the degradation of bisphenol A and other related endocrine disrupting compounds. Various redox mediators, surfactants and additives have also enhanced enzymatic oxidation of bisphenol A and other related endocrine disrupting compounds.